Divers Alert! - Nanette Holland; Linda Walters; Charles Jacoby (EDIS)
FA129, a 2-page full color fact sheet by Nanette Holland, Linda Walters and Charles Jacoby, helps divers identify some known and potential introduced species in Florida, and it provides a contact for reporting sightings of these species. Published by the UF Department of Fisheries and Aquatic Sciences, December 2006.